Use of bisphosphonates among women and risk of atrial fibrillation and flutter: population based case-control study. Issue 7648 (11th March 2008) - Sørensen, Henrik Toft; Christensen, Steffen; Mehnert, Frank; Pedersen, Lars; Chapurlat, Roland D; Cummings, Steven R; Baron, John A
Abstract : Objective To assess the association between atrial fibrillation and flutter and use of bisphosphonates for osteoporosis among women. Design Population based case-control study, using medical databases from Denmark. Setting Northern Denmark. Participants 13 586 patients with atrial fibrillation and flutter and 68 054 population controls, all with complete hospital and prescription history. Main outcome measure Adjusted relative risk of atrial fibrillation and flutter. Results 435 cases (3.2%) and 1958 population controls (2.9%) were current users of bisphosphonates for osteoporosis. Etidronate and alendronate were used with almost the same frequency among cases and controls. The adjusted relative risk of current use of bisphosphonates compared with non-use was 0.95 (95% confidence interval 0.84 to 1.07). New users had a relative risk of 0.75 (95% confidence interval 0.49 to 1.16), broadly similar to the estimate for continuing users (relative risk 0.96, 95% confidence interval 0.85 to 1.09). The relative risk estimates were independent of number of prescriptions and the position of the atrial fibrillation and flutter diagnosis in the discharge record, and were similar for inpatients and outpatients. Conclusion No evidence was found that use of bisphosphonates increases the risk of atrial fibrillation and flutter.